The impact of graphic novels on Malaysian Secondary School ESL learners’ reading comprehension / Nadia Mohd Dani Goh - Nadia, Mohd Dani Goh (2017)
Based on PISA 2009, 2012, and 2015, Malaysian reading literacy rate is at a worrying state. The Ministry of Education has made a move to use graphic novels as a part of its literature component in schools which is a great way in increasing reading literacy. This raised two sides of arguments pertaining to the use of graphic novels in language learning: one supports while the other disapproves. This study seeks to explore the impact of reading graphic novels on ESL learners‟ reading comprehension. An explanatory mixed methods design is adopted. It comprises two phases: Reading comprehension tests for descriptive statistics (The first test used the text-only novel while the second test used the graphic novel) and one-to-one interviews. 60 students participated in the study with results showing that reading graphic novel has a positive impact on ESL learners‟ reading comprehension. From the interviews, two elements were found to be overarching the factors: the reader (positive perception of text format, positive affect, effective reading strategies, linguistic knowledge and visual literacy skills) and the stimuli (visual and verbal in relation to cognition). Learners stated that reading graphic novels helped them: retain the story in their memory better, imagine and compensate lack of imagination, have a clearer picture of characters and the storyline, and boost their reading motivation. Via graphic novels, readers were allowed to oscillate between verbal and visual elements and these findings were in support of Paivio‟s Dual Coding Theory (DCT) which involves two systems (verbal and nonverbal) working together, leading towards better storage of information and accelerating the process of activating logogens and imagens. On a different note, there were a few readers, representing the minority, who preferred and performed better without graphics due to lack of visual literacy skills and ineffective reading strategies.